Students' satisfaction towards academic library services / Wan Nor Haliza Wan Mokhtar and Nur Sofea Adila Mohd Yusof - Wan Mokhtar, Wan Nor Haliza; Mohd Yusof, Sofea Adila (Universiti Teknologi MARA, 2020)
In PTAR, UiTM Puncak Perdana, the librarian always showing their best in promoting the library's services. There are so many activities that have been done to attract more users to the library. Such as workshop training, public relations activity, Open Public Access Catalogue (OPAC) and so on. Unfortunately, they still lack their performance because they need to compete with the new technology where the range of services outside the physical library is expanding. The purpose of this paper is to investigate the students' satisfaction towards library services. The logical limitation of this study is the population. Due to the time and budget limitation, researcher will just be able to study in the context of PTAR academic's library only. The data are collected through a survey by using structured questionnaires which has been disseminated to 250 students. The major findings of this study conducted on students' satisfaction with library services a study of Tun Abdul Razak Library (PTAR), UiTM Puncak Perdana revealed that library users were satisfied with the following library services such as lending services, renewal of library materials, longer hours of internet services in the library, suitable opening hours, downloading and printing of online resource services.